Alternative splicing and its regulation in the malaria vector Anopheles gambiae - Díaz-Terenti, Bárbara; Ruiz, José Luis; Gómez-Díaz, Elena (Frontiers in Malaria, 2024)
Alternative splicing (AS) is a highly conserved mechanism that allows for the expansion of the coding capacity of the genome, through modifications of the way that multiple isoforms are expressed or used to generate different phenotypes. Despite its importance in physiology and disease, genome-wide studies of AS are lacking in most insects, including mosquitoes. Even for model organisms, chromatin associated processes involved in the regulation AS are poorly known. In this study, we investigated AS in the mosquito Anopheles gambiae in the context of tissue-specific gene expression and mosquito responses to a Plasmodium falciparum infection, as well as the relationship between patterns of differential isoform expression and usage with chromatin accessibility changes. For this, we combined RNA-seq and ATAC-seq data from A. gambiae midguts and salivary glands, infected and non-infected. We first report differences between tissues in the expression of 392 isoforms and in the use of 247 isoforms. Secondly, we find a clear and significant association between chromatin accessibility states and tissue-specific patterns of AS. The analysis of differential accessible regions located at splicing sites led to the identification of several motifs resembling the binding sites of Drosophila transcription factors. Finally, the genome-wide analysis of tissue-dependent enhancer activity revealed that approximately 20% of A. gambiae transcriptional enhancers annotate to a differentially expressed or used isoform, and that their activation status is linked to AS differences between tissues. This research elucidates the role of AS in mosquito vector gene expression and identifies regulatory regions potentially involved in AS regulation, which could be important in the development of novel strategies for vector control.